2005
DOI: 10.1111/j.1572-0241.2005.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Colorectal Obstruction Treated by Means of Transanal Drainage Tube: Effectiveness Before Surgery and Stenting

Abstract: Management of acute colorectal obstruction using the DCT was found to be effective and safe, irrespective of the site or etiology of the obstruction. Therefore, this procedure should be considered as a primary method for decompression of the obstructed colon before considering surgery or stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 17 publications
1
38
0
5
Order By: Relevance
“…A simple comparison of cost for a one‐stage operation with a TDT versus a bridge to surgery with a SEMS is impossible because preoperative management with a TDT requires admission for several weeks before surgery. However, several studies have shown that the cost of a TDT ($500) is much lower than the cost of a SEMS ($2000) 9, 10, 20. Furthermore, in patients undergoing management with a TDT, combined nutritional therapy involving an LRD and PPN can reduce the cost of nutritional management compared with TPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple comparison of cost for a one‐stage operation with a TDT versus a bridge to surgery with a SEMS is impossible because preoperative management with a TDT requires admission for several weeks before surgery. However, several studies have shown that the cost of a TDT ($500) is much lower than the cost of a SEMS ($2000) 9, 10, 20. Furthermore, in patients undergoing management with a TDT, combined nutritional therapy involving an LRD and PPN can reduce the cost of nutritional management compared with TPN.…”
Section: Discussionmentioning
confidence: 99%
“…The best surgical treatment for acute malignant left‐sided large bowel obstruction remains controversial. However, elective one‐stage resection and anastomosis after decompression with a transanal drainage tube (TDT) or a self‐expandable metal stent (SEMS) are expected to improve the postoperative outcome 7, 8, 9, 10, 11. The mortality rate for patients with colorectal cancer undergoing emergency surgery reportedly ranges from 8% to 15%, compared with 3% to 6% mortality in those undergoing elective surgery 4, 6, 12…”
Section: Introductionmentioning
confidence: 99%
“…Recently, regardless of the site of colorectal obstruction, the development of a new transanal drainage tube and techniques for its use has made it possible to decompress acute colorectal obstruction [2][3][4] . Several advantages of this method have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In 5 series consisting of 153 patients with acute colonic obstruction treated with transanal decompression tube placement, two cases of bowel perforation occurred (1.3%) [86][87][88][89][90].…”
Section: Colonic Decompression Tube Placementsmentioning
confidence: 99%